2016
DOI: 10.1002/alr.21800
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal improvement and stability of olfactory function in the evaluation of surgical management for chronic rhinosinusitis

Abstract: BACKGROUND Abnormal olfaction is common with chronic rhinosinusitis (CRS) and associates with various measures of sinonasal inflammation. The Brief Smell Identification Test (BSIT) has demonstrated improvements in abnormal olfactory detection following endoscopic sinus surgery (ESS), but olfaction remains understudied using this instrument. Discerning longitudinal, postoperative durability in olfaction is critical for patient counseling. METHODS Adult participants with medically recalcitrant CRS were prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…Some studies added longer follow‐up periods after a 6‐month evaluation . Here, the improvement in olfaction that was found after 3.5 and 6 months, respectively, was stable over a period of 12 to 18 months, except in patients with polyps and asthma who began to show another decrease in olfaction …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Some studies added longer follow‐up periods after a 6‐month evaluation . Here, the improvement in olfaction that was found after 3.5 and 6 months, respectively, was stable over a period of 12 to 18 months, except in patients with polyps and asthma who began to show another decrease in olfaction …”
Section: Resultsmentioning
confidence: 94%
“…Six studies reported on the influence of the preoperative status of olfaction . If anosmia was present, this led to an improvement in sense of smell after surgery in all six studies.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Study data was manually entered into a HIPAA compliant relational database (Access, Microsoft Corp., Redmond, WA) and statistical analyses were conducted using commercial software (SPSS v.23, IBM Corp., Armonk, NY). Last available SNOT-22, BSIT, and endoscopy scores were used to operationalize postoperative evaluations due to previously reported similarity of mean postoperative scores between 6, 12, and 18 month follow-up in this cohort 21,22 Postoperative improvement was determined by subtracting preoperative scores from postoperative scores and averaged. Descriptive analytics are reported while comparisons in preoperative measures while between-group differences were evaluated using either two-sided independent sample t-tests, Mann-Whitney U tests, or Pearson’s chi-square testing, based on scale distribution or count frequency.…”
Section: Methodsmentioning
confidence: 99%